Evaluasi Sistem Pengendalian Internal Pemerintah Dalam Pengeluaran Kas Pada Bagian Pemerintahan Dan Kesejahteraan Rakyat Kota Surabaya - Leo Rizki Mubarak; Hero Priono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine and evaluate the government's internal control system and cash expenditure procedures in the Government and People's Welfare Section of Surabaya City are in accordance with applicable regulations or not. This research was carried out at the Surabaya City Government and People's Welfare Office located in the Genteng Village government building, Genteng District, Surabaya City. The analytical method used in this study is the Descriptive Analysis Method. The data collection techniques used are observation, in-depth interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results showed that the Cash Expenditure System and Procedure implemented in the Government and People's Welfare Section of Surabaya City has been running well in accordance with Permendagri Number 13 of 2006 concerning Regional Financial Management Guidelines. The internal control system of cash expenditure in the Government and People's Welfare Section of Surabaya City has also been implemented well but has not been maximally marked by the lack of maximum implementation of policies on human resource development so that employees are still found who lack mastery related to cash expenditures and the constraints of the duties of the finance and accounting department.